Forecasting and Risk Management Techniques for Electricity Markets - Yamada, Yuji (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book focuses on the recent development of forecasting and risk management techniques for electricity markets. In addition, we discuss research on new trading platforms and environments using blockchain-based peer-to-peer (P2P) markets and computer agents. The book consists of two parts. The first part is entitled "Forecasting and Risk Management Techniques" and contains five chapters related to weather and electricity derivatives, and load and price forecasting for supporting electricity trading. The second part is entitled "Peer-to-Peer (P2P) Electricity Trading System and Strategy" and contains the following five chapters related to the feasibility and enhancement of P2P energy trading from various aspects.